Pengaruh Kualitas Produk dan Pelayanan terhadap Keputusan Pembelian Spare Part di PT. Apexindo Perkasa - Yayang Wulandini; Rhoma Iskandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the influence of product and service quality on spare part purchasing decisions at PT. Apexindo Perkasa. The population in this study were all customers at PT. Apexindo Perkasa. Data collection techniques use questionnaires and literatur study. The data analysis techniquen is quantitative. The results of this research show that there is no partial positive and significant effect between product quality on purchasing decisions as evidenced by the regression coefficient value of 0.118, t value of 0.970 and significance value of 0.336; there is a partial positive and significant influence between service on purchasing decisions as evidenced by a regression coefficient value of 0.623, a calculated t value of 3.305 and a significance value of 0.002; there is a simultaneous positive and significant influence between product quality and service on purchasing decisions, proven by The calculated f value is 45.570 and the significance value is 0.000. Purchasing decisions are influenced by product and service quality by 56.4% and the remaining 43.6 are influenced by other variables not examined in this research.